Derivatives Demystified: Unmasking Conceptual Difficulties - Kafle, Sujan (Journal of Research and Development, 2026)
Derivatives Demystified: Unmasking Conceptual Difficulties Sujan Kafle1 Abstract This case study is related to "conceptual difficulties in learning derivative" that explores the difficulties of conceptual understanding of derivative. The study is based on data from purposively selected 40 students of grade XI at Makwanpur Multiple Campus, Makwanpur. The data were collected through the CPUBT and interview guidelines. Four problems were asked in the CPUBT which was constructed based on APOS theory. Based on test result, three respondents were selected for interview and the in depth interview was conducted. The information collected through the interview was systematized and analyzed according to general inductive method. The finding of this study indicates that students had weak concept to understand the derivative as a rate of change, unable to understand the clear geometrical meaning of derivative, unable to make exact sense of limit necessary to study the derivative. Hence, it can be concluded that both teacher and students should focus the conceptual teaching and learning of derivative and pre knowledge of derivative such that they could easily understand the concept of derivative. Thus, teacher should change their teaching style so they can make their classroom very fruitful and learning derivative become a meaningful which avoids the rote learning.